Cardiocerebrovascular benefits of early rhythm control in patients with atrial fibrillation detected after stroke: a systematic review and meta-analysis - Ma, Liang; Wang, Baofu; Fan, Jiasai; Zhou, Hufang; Li, Jingen; Li, Weisheng; Zheng, Xiangying; Wang, Xian (Frontiers in Cardiovascular Medicine, 2024)
Objective This study aimed to evaluate the impact of early rhythm control (ERC) on the occurrence of cardiocerebrovascular events in patients diagnosed with atrial fibrillation detected after stroke (AFDAS). Methods A systematic search was conducted across nine databases from inception to October 15, 2023 to identify clinical trials comparing ERC with usual care interventions in AFDAS patients. The primary outcome assessed was recurrent stroke, with secondary outcomes including all-cause mortality, adverse events related to arrhythmias, and dementia. Results Analysis of five studies, consisting of two randomized clinical trials (RCTs) involving 490 patients and three cohort studies involving 95,019 patients, revealed a reduced rate of recurrent stroke [odds ratio (OR) = 0.30, 95% confidence interval (CI) 0.11–0.80, P = 0.016 in RCTs; OR = 0.64, 95% CI 0.61–0.68, P < 0.00001 in cohort studies] and all-cause mortality (hazards ratio = 0.94, 95% CI 0.90–0.98, P = 0.005 in cohort studies) in the ERC group compared to the usual care group. In addition, ERC was associated with superior outcomes in terms of dementia. Conclusions Patients with AFDAS who underwent ERC treatment exhibited a decreased risk of cardiocerebrovascular events compared to those receiving usual care. These results support the potential benefits of implementing an ERC strategy for this specific patient population. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, Identifier [CRD42023465994].